FROM HADITH TO HEALTH: Contextualizing the One-Third Eating Principle in Light of Modern Nutritional Science - Hildayana, Tri; Darta, Ali (RIWAYAH, 2025)
This study investigates the integration of Hadith teachings on dietary practices with modern nutritional science within the Muslim community of Tanjung Morawa B Village. Employing an ethnographic approach, the research draws on in-depth interviews with 40 respondents and participatory observations of 20 individuals. The findings reveal that 77.5% of participants practice the "one-third" eating principle—eating before hunger intensifies, stopping before fullness, and dining before Maghrib. These habits align with contemporary nutritional strategies such as portion control and time-restricted eating, both of which contribute to metabolic health. Notably, despite 65% of respondents coming from economically disadvantaged backgrounds, they maintain healthy diets rooted in religious values by utilizing accessible local foods like pumpkin, cassava, and legumes. The study also notes adaptive strategies for health conditions such as gastritis, reflecting the principle’s flexibility. Overall, the research underscores the potential of integrating religious principles with modern health frameworks, offering a culturally relevant model for dietary intervention in Muslim communities.[Penelitian ini mengkaji integrasi ajaran hadis tentang pola makan dengan ilmu gizi modern dalam konteks komunitas Muslim di Desa Tanjung Morawa B. Dengan menggunakan pendekatan etnografi, penelitian ini melibatkan wawancara mendalam terhadap 40 responden dan observasi partisipatif terhadap 20 di antaranya. Hasil temuan menunjukkan bahwa 77,5% responden menerapkan prinsip makan sepertiga—makan sebelum merasa lapar, berhenti sebelum kenyang, serta makan malam sebelum Maghrib. Pola ini selaras dengan konsep gizi modern seperti pengendalian porsi dan pola makan dengan waktu terbatas (time-restricted eating) yang terbukti mendukung kesehatan metabolik. Meskipun 65% responden berasal dari keluarga kurang mampu, mereka tetap menjaga pola makan sehat yang berlandaskan nilai-nilai keagamaan dengan memanfaatkan pangan lokal seperti labu, singkong, dan kacang-kacangan. Penelitian ini juga mencatat adanya penyesuaian terhadap kondisi kesehatan tertentu seperti gastritis, yang menunjukkan fleksibilitas prinsip ini. Secara keseluruhan, penelitian ini menegaskan pentingnya integrasi nilai-nilai religius dengan pendekatan kesehatan modern, serta menawarkan model intervensi gizi yang kontekstual bagi komunitas Muslim guna meningkatkan kesejahteraan mereka.]